Choosing to Study Human Development and Family Science. - Black, Sara M.; Linneman, Emma; Quitorio, Gwyneth; Vang, Maichong; Dyer, Kathleen (Marriage & Family Review)
Previous research reports that undergraduate students in Human Development and Family Science (HDFS) programs are motivated more by an interest in the content area and a general desire to be helpful than by specific career goals. Some have speculated that HDFS is a "discovery major": one that students stumble upon accidentally while in college rather than being motivated to attend college specifically to pursue that course of study. The two studies reported here were designed to explore these possibilities. Study 1 surveys current students (n = 129) in HDFS programs in the California State University (CSU) system, and interviews a subset (n = 17) of that sample. Study 2 surveys current HDFS students (n = 47) along with students in other social science programs (n = 226) at one CSU campus. Results indicate that students select HDFS because they recognize its applicability to everyday life, its importance in society, and its personal relevance to their own lives; HDFS students are not generally driven by specific career goals. In addition, about 45% of HDFS students discovered the major after starting college – this is similar to the rate of "discovery majors" in other social sciences. Discovery majors are less likely to pursue work as preschool or elementary school teachers, and more likely to be transfers from community college, but this history of "discovery" is unrelated to their sense of belongingness, their satisfaction, and their success in the program.